Public expenditure proposal for rural areas - Casco, Andrés; Romero, José (Estudios Económicos de El Colegio de México, 1997)
This paper proposes both expenditures in public works and for an aggressive educational program for rural areas. It first analyzes the cost benefit of agricultural price supports and concludes that this method of fighting poverty is very expensive; i.e., the benefit obtained for each peso expended in these program is less than 50%, and even lower for small producers. Then the paper analyzed the cost benefit of eliminating those programs and their substitution with a program of direct payments to producers. The benefits of this program are significant, but these benefits are not distributed evenly, and rural workers lose in absolute terms.